Economic Downturns and the Informativeness of Management Earnings Forecasts - MASLAR, DAVID A.; SERFLING, MATTHEW; SHAIKH, SARAH (Journal of Accounting Research, 2021)
ABSTRACT Economic downturns create uncertainty about a firm's operations and make it disproportionately harder for outside market participants to assess the firm's prospects. We posit that in this environment, management earnings forecasts will be more informative to investors and analysts. Consistent with this prediction, we find larger stock price reactions and analyst forecast revisions to news in management forecasts during downturns. Holding the amount of news in forecasts constant, stock price reactions to management forecasts are also greater than those to analyst forecasts. We also find that relative to analyst forecasts, management forecast accuracy increases during downturns, suggesting that investors justifiably assess management forecasts as more informative. Overall, we document that macroeconomic conditions create time‐series variation in the informativeness of different sources of information to outside market participants.